The relationship between quality of nursing work life (QNWL) and job satisfaction in the central surgery unit (CSU) - Nugroho, Anwar Arief; Abdurrouf, Muhammad; Sari, Dyah Wiji Puspita (JOURNAL OF Mental Health Concerns, 2026)
Background: The Central Surgical Installation (IBS) represents a clinical unit with intensive workload demands, where nurses’ Quality of Nursing Work Life (QNWL) plays a critical role in shaping job satisfaction and maintaining service sustainability. Purpose: To identify the relationship between QNWL and job satisfaction among staff nurses working in the IBS. Method: A quantitative correlational study with a cross-sectional design was employed. The sample consisted of 128 staff nurses selected through simple random sampling. Data collection utilized a 41-item QNWL questionnaire and a 20-item job satisfaction questionnaire, followed by descriptive analysis and Spearman correlation testing. Results: QNWL was predominantly categorized as good (mean 153.88±16.01), while job satisfaction was generally at a moderate level (mean 70.69±11.42). Spearman correlation analysis revealed a strong and statistically significant positive relationship between QNWL and job satisfaction (r_s=0.647; p<0.001). Conclusion: These findings indicate that enhancing QNWL through organizational support, improved job design, and healthier workload and scheduling management can contribute to higher levels of job satisfaction among nurses working in high-pressure units such as the IBS Keywords: Job Satisfaction; Nursing Management; Operating Room; Quality of Nursing Work Life; Staff Nurses.